Comparison Of Self Directed Video And Simulation Methods On Hand Only CPR Skill - Azizah, Nanda Putri Nur; Adhi, M.Hanif Prasetya; Suparti, Sri; Fatwati, Nurul Fitriana (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Current data shows that most cases of cardiac arrest occur outside the hospital, the mortality rate is almost 90%. Indonesia is in second place in the Asian continent after the Philippines with 317,000 people suffering from heart disease.Objective:  The purpose of this study was to determine the effect of providing education and simulation of hand-only CPR on the level of skills through the self-Directed Video method and simulation in students of SMA Muhammadiyah Tambak-Banyumas.Method: The method used is Quasi Experimental with a pre-test and post-test control group design approach. The instrument used in this study was an observation sheet to measure the level of skills about hand-only CPR.Result: The results of the study showed the effect of differences in the comparison of the self-directed video and simulation methods on hand-only CPR skills with a posttest value of self-directed video 79.00 and simulation 70.00. Conclusion: This shows that training using the self-directed video method has a greater effect on hand-only CPR skills compared to the simulation method in students of SMA Muhammadiyah Tambak-Banyumas.